PRE-NURSERY OF SHRIMP POST-LARVAE REARED IN BIOFLOC SYSTEM UNDER DIFFERENT STOCKING DENSITIES - Priscila Costa Rezende; Delano Dias Schleder; Walter Quadros Seiffert; Edemar Roberto Andreatta; Felipe Nascimento Vieira (Boletim do Instituto de Pesca)
This study evaluated different stocking densities during pre-nursery of Pacific white shrimp post‑larvae (PL) reared in a biofloc system. The tanks (60 L) were stocked with PL stage 5 (PL 5) under five densities (80, 100, 120, 140 and 160 PLs L-1), in triplicate, resulting in 15 experimental units. PLs were fed nine times a day using commercial feed. Molasses was added in all treatments four times a day at an average carbon: nitrogen ratio of 14.7: 1. The experiment was carried out until the PLs reached PL 20 stage, and during this time, water quality variables, survival, weight gain and survival to salinity stress were all evaluated. For treatments above 100 PLs L-1, total suspended solids were higher than recommended (700 mg L-1). Also, the treatment with 160 PL L-1 had higher total ammonia nitrogen peaks (>10 mg L-1), resulting in lower survival in this treatment. No differences were observed between treatments in the other performance parameters evaluated (final weight and survival to salinity stress). It was concluded that pre-nursery of Pacific white shrimp can be performed using densities up to 140 post-larvae L-1 in a biofloc system without compromising shrimp growth performance.